Correction by Focus: Cleft Constructions and the Cross-Linguistic Variation in Phonological Form - Greif, Markus; Skopeteas, Stavros (Frontiers in Psychology, 2021)
A challenging issue of cross-linguistic variation is that the same syntactic construction may appear in different arrays of contexts depending on language. For instance, cleft constructions appear with contrastive focus in English, but in a larger array of contexts in French. A part of the cross-linguistic variation may be due to prosodic differences, since prosodic possibilities determine the array of focus structures that can be mapped onto one and the same syntactic configuration. In the present study, we compare languages with flexible nuclear-accent placement (English, German), with languages that do not use this prosodic strategy (French, Mandarin Chinese). In a speech production experiment, we examine the prosodic realization of contrastive focus to identify prosodic reflexes of focus in all languages. The presence of different phonetic reflexes of focus suggests that – anything else being equal – the same syntactic constructions should be possible in the same array of contexts. In an acceptability study with written questionnaires, we examined the felicity of cleft constructions in contexts licensing a focus within the cleft clause. This focus structure is orthogonal to the preferred focus structure of cleft constructions and can appear in cases of second-occurrence foci (in contexts of correction). The obtained judgments reveal a distinction between languages with flexible nuclear-accent placement (English, German) and languages with other types of reflexes of focus (French, Chinese): languages of the former type have an advantage in using cleft constructions with a focus within the cleft clause, which shows that the array of contexts of using clefts in English and German is not a proper subset of the array of contexts applying to the same constructions in French and Chinese. The obtained differences can be explained by the role of prosodic devices and corroborate the view that prosodic reflexes of focus have different semantic-pragmatic import: it is easier to establish a focus structure that is orthogonal to the syntax in a language with flexible nuclear-accent placement (English, German); this does not hold for prosodic correlates of focus that reinforce the articulation of prosodic constituents (French) or the articulation of lexical tones (Chinese).